2020
DOI: 10.1302/2633-1462.110.bjo-2020-0106.r1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 lockdown on orthopaedic emergency presentations in a remote and rural population

Abstract: Aims COVID-19 remains the major focus of healthcare provision. Managing orthopaedic emergencies effectively, while at the same time protecting patients and staff, remains a challenge. We explore how the UK lockdown affected the rate, distribution, and type of orthopaedic emergency department (ED) presentations, using the same period in 2019 as reference. This article discusses considerations for the ED and trauma wards to help to maintain the safety of patients and healthcare providers with an emphasis on more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 6 publications
(5 reference statements)
1
13
0
1
Order By: Relevance
“…The 34% reduction in acute trauma referrals is in keeping with previous single-centre studies performed in the UK with results ranging between 26% and 59% 10–13 15 16. As described in these previous studies, we would attribute the overall reduction of trauma workload to be due to reduction in travel and outdoor activities during the national lockdown.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The 34% reduction in acute trauma referrals is in keeping with previous single-centre studies performed in the UK with results ranging between 26% and 59% 10–13 15 16. As described in these previous studies, we would attribute the overall reduction of trauma workload to be due to reduction in travel and outdoor activities during the national lockdown.…”
Section: Discussionsupporting
confidence: 85%
“…The lockdown to limit the spread of the virus has had an unforeseen effect in significantly reducing the acute trauma workload described in several singlecentre studies. [10][11][12][13] There has, however, not been a British multicentre reflection of the impact of the COVID-19 pandemic on the orthopaedic workload and its potential impact on patient mortality.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in fractures of elderly patients was also seen at a hospital in Inverness, Scotland. 19…”
Section: Existing Literaturementioning
confidence: 99%
“…A study in the UK focused on orthopedic emergencies, during lockdown, showed that patient visits had a decrease of 58.6%. The orthopedic presentations in 2020 and 2019 were 736 (37.2%) and 1729 (36.2%), a decrease of 57.4% [11]. An orthopedic team in the UK set up a 7-day "One-Stop" clinic for minor injuries/ ambulatory patients.…”
Section: Europementioning
confidence: 99%